Lameness and its impact on welfare of cattle - Jan K. Shearer (Universidad de Antioquia, 2017)
Ulcers, white line disease, and traumatic lesions of the sole are common lameness disorders in dairy cattle. Since they are often associated with abscess formation, many assume that topical antibiotic therapy is required. In fact, topical therapy is unlikely to be of value and violates one of the principal precepts of bioethics in medicine “first, do no harm”.  The first step in developing a rational treatment strategy is to understand the pathogenesis of lameness conditions and wound healing in animals; otherwise, therapy is likely to interfere with, rather than compliment, the healing process. Finally, while much of our attention is directed at the specific treatment of hoof lesions, it is important to remember that lameness disorders are one of the most painful of health disorders in cattle. Therefore, in addition to early detection of lameness, treatment of lame cows must include considerations for pain management.